A Novel System for Constructing a Recombinant Highly-Attenuated Vaccinia Virus Strain (LC16m8) Expressing Foreign Genes and Its Application for the Generation of LC16m8-Based Vaccines against Herpes Simplex Virus 2 - Omura, Natsumi; Yoshikawa, Tomoki; Fujii, Hikaru; Shibamura, Miho; Inagaki, Takuya; Kato, Hirofumi; Egawa, Kazutaka; Harada, Shizuko; Yamada, Souichi; Takeyama, Haruko; Saijo, Masayuki (Japanese Journal of Infectious Diseases, 2018)
A novel system was developed for generating highly attenuated vaccinia virus LC16m8 (m8, third-generation smallpox vaccine) that expresses foreign genes. The innovations in this system are its excisable selection marker, specificity of the integration site of a gene of interest, and easy identification of clones with a fluorescent signal. Using this system, recombinant m8s, which expressed herpes simplex virus 2 (HSV-2) glycoprotein B (gB)-, gD-, or both gB and gD (gB + gD), were generated, and their efficacy was evaluated. First, the induction of a specific IgG against these HSV-2 glycoproteins in mice infected with one of these recombinant m8s was confirmed by an immunofluorescent assay. Next, mice preinfected with one of the recombinant m8s were infected with HSV-2 at a lethal dose to examine the vaccine efficacy. The fatality rate among the mice preinfected with either the recombinant gB + gD- or gD-expressing m8 significantly decreased in comparison with the control. The survival rate in male and female mice preinfected with either the recombinant gB + gD- or gD-expressing m8 increased to 100% and 60%, respectively, while most of the control mice died. In summary, this new system may be applicable to creation of a novel m8-based vaccine.